An interdisciplinary One Health case study for high school students - Ioerger, Nicole (Kansas State University, 2020)
One Health is a term used to describe the interconnectedness of human, animal, and environmental health. Those individuals who work on solving One Health issues, such as the spread of zoonotic diseases, must be well-trained in their own disciplines but must also be able to work as members of interdisciplinary teams. It is important that students at the high school and college levels are introduced to these concepts so that they have the appropriate critical thinking and social skills to help solve One Health issues when they enter the workforce. There are currently very few One Health lesson plan resources available for high school teachers and students. This report provides the rationale for teaching high school students about the One Health approach to solving global health issues through an interdisciplinary case study. The case study, which is centered around a theoretical outbreak of Rift Valley fever virus, can easily be incorporated into biology, animal science, or health courses and is aligned with several of the One Health core competencies suggested by the National Academy of Medicine.
Keywords: One Health; case study; high school; interdisciplinary; education